2017
DOI: 10.1097/hco.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations and cardiovascular disease

Abstract: Purpose of Review Cardiovascular disease (CVD) is responsible for more morbidity and mortality worldwide than any other ailment. Strategies for reducing CVD prevalence must involve identification of individuals at high risk for these diseases, and the prevention of its initial development. Such preventative efforts are currently limited by an incomplete understanding of the genetic determinants of CVD risk. In this review, evidence for the involvement of inherited mitochondrial mutations in development of CVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 98 publications
0
51
0
Order By: Relevance
“…Although PH can be caused by chronic liver disease and portal hypertension, PH after LT is infrequent; PH has also been reported in patients with primary mitochondrial diseases (e.g. m.3243A>G, NFU1, BOLA3) 38,39 , though the mechanism underlying this remains unknown. In addition to the two patients who initially presented with HCC in this study, three MPV17-deficient patients developed HCC 27,35,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Although PH can be caused by chronic liver disease and portal hypertension, PH after LT is infrequent; PH has also been reported in patients with primary mitochondrial diseases (e.g. m.3243A>G, NFU1, BOLA3) 38,39 , though the mechanism underlying this remains unknown. In addition to the two patients who initially presented with HCC in this study, three MPV17-deficient patients developed HCC 27,35,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial diseases are common inherited neurological disorders, in which cardiac manifestations are among the core features [5,28]. The incidence of major adverse cardiac events has been reported to be increased especially among patients harbouring the m.3243A > G mutation or a single mtDNA deletion [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial diseases can manifest as cardiomyopathy, conduction defects and even SCD [5]. The m.3243A > G point mutation in the MT-TL1 gene is the most common pathogenic mtDNA mutation and causes variable clinical manifestations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, crossing MNX mice with mice over-expressing the HER2/Neu oncogene, we observed driver-dependent alterations in tumorigenesis and metastasis [62]. While not the focus of this review per se , MNX mice have uncovered existence of mtDNA modifier loci in cardiovascular disease [61], atherosclerosis [61,64], and obesity [63], strongly supporting a closer look at mitochondrial quantitative trait loci [65,66]. Early studies to dissect the molecular mechanisms identified significant and, importantly, selective changes in the methylation patterns and gene expression profiles of wild-type and MNX mice [63].…”
Section: Mitochondrial Dna and Metastasismentioning
confidence: 91%